Celiac Disease After Administration of Immune Checkpoint Inhibitors: A Case Report - Leblanc, Julie; Hoibian, Solene; Boucraut, Agathe; Ratone, Jean-Philippe; Stoffaes, Louis; Dano, Domitille; Louvel-Perrot, Delphine; Chanez, Brice; Chretien, Anne-Sophie; Madroszyk, Anne; Rochigneux, Philippe (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors (ICI) reinvigorate immune system to recognize and destroy tumor cells. Because of this biological mechanism, patients might develop auto-immune toxicities, notably in digestive tract (most frequently, hepatitis or colitis). A 70-year old man with relapsed mesothelioma was treated by Nivolumab in 3rd line. He was hospitalized for watery and foul smelling diarrhea. He underwent gastro-intestinal endoscopy showing duodenitis and villous atrophy and measurement of serum IgA antibodies to tissue transglutaminase (tTG-IgA+), leading to the diagnosis of ICI-induced celiac disease. He was treated by steroids, proton pump inhibitor and gluten-free diet. If ICI-induced celiac disease is rare in the literature, increasing reports suggest that celiac disease might represent an under-estimated ICI toxicity. This case highlights the necessity of complementary investigation (including tTG-IgA and endoscopic biopsies) in patients with atypical digestive symptoms during immunotherapy.